Sabahan Porridge Enterprise - Asin, Marcella; Kumpot, Jureon; Puasa, Sylvia; Boikos, Shairley Jane; Jackson, Sherly (2015)
This Business Proposal attempts to present the fundamental concept and practicing entrepreneurship in an easy-to-understand manner. It focuses on theories and practices entrepreneurship that we had studied and done our research. It is divided into four chapters. Chapter one provides an overview entire of administration management and business background. Specification an Autocratic administration style and apply functional organization structure. At the end of this chapter, the reader will recognize the characteristics of our operational functions, organizational principals and business structure. Chapter two covers the aspect of Marketing. For important topics on marketing discussed is such as understanding the marketing definition and strategy, defining the major preparing a marketing plan, and managing marketing activities. The scope of operations management is presented in chapter three. The discussion chapter emphasize on the fundamental aspects of operations planning. In this respect, this chapter focused on the function of operations management on exportation trade. Chapter four introduces the process of financial planning for a new business. This begins with a discussion on the relationship between operating budget and financial budget. Then, we illustrate the various steps that we choose which the reader can take in developing financial plan. As a result of the planning process, the readers can determine their financial cash flow needs in order to start a new venture. After reviewing the types and sources of potential financing, we explain three important tools that can be used to analyze the firm's viability of the business. For example, pro forma cash flow statement, pro forma income statement and pro forma balance sheet. The chapter concludes with a review of some of the techniques examining financial statement to help readers and analyze the financial position and purpose of the business. Fundamental of Entrepreneurship is a dynamic subject it goes without saying that entrepreneurships takes need constant updating. Business proposal is crucial because it has the ability of entrepreneur or feasibility to start the business.